Nighttime mesospheric ozone enhancements during the 2002 southern hemispheric major stratospheric warming. (March 2018) - Smith-Johnsen, Christine; Orsolini, Yvan; Stordal, Frode; Limpasuvan, Varavut; Pérot, Kristell
Abstract: Sudden Stratospheric Warmings (SSW) affect the chemistry and dynamics of the middle atmosphere. Major warmings occur roughly every second winter in the Northern Hemisphere (NH), but has only been observed once in the Southern Hemisphere (SH), during the Antarctic winter of 2002. Observations by the Global Ozone Monitoring by Occultation of Stars (GOMOS, an instrument on board Envisat) during this rare event, show a 40% increase of ozone in the nighttime secondary ozone layer at subpolar latitudes compared to non-SSW years. This study investigates the cause of the mesospheric nighttime ozone increase, using the National Center for Atmospheric Research (NCAR) Whole Atmosphere Community Climate Model with specified dynamics (SD-WACCM). The 2002 SH winter was characterized by several reductions of the strength of the polar night jet in the upper stratosphere before the jet reversed completely, marking the onset of the major SSW. At the time of these wind reductions, corresponding episodic increases can be seen in the modelled nighttime secondary ozone layer. This ozone increase is attributed largely to enhanced upwelling and the associated cooling of the altitude region in conjunction with the wind reversal. This is in correspondence to similar studies of SSW induced ozone enhancements in NH. But unlike its NH counterpart, the SH secondary ozone layer appeared to be impacted less by episodic variations in atomic hydrogen. Seasonally decreasing atomic hydrogen plays however a larger role in SH compared to NH. Highlights: The 2002 SH winter includes several reductions of the polar night jet, before a complete reversion indicate a major SSW. At the time of the wind reductions, corresponding episodic increase is found in the modeled nighttime mesospheric ozone. The ozone increases are attributed to enhanced upwelling and associated mesospheric cooling. Our findings are in correspondence to similar studies of SSW induced ozone enhancements in NH. Compared to its NH counterpart, the SH secondary ozone layer appeared to be impacted less by variations in atomic hydrogen.